2004
DOI: 10.1002/adma.200400179
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Shell‐Shaped Carbon Nanoparticles Above a Critical Laser Power in Irradiated Acetylene

Abstract: In the last two decades, a series of novel nanostructured carbon materials have been synthesized in the laboratory, [1] including carbon nanotubes, [2] carbon onions, [3] and carbon nanocapsules. [4,5] Intensive studies of nanostructured carbon synthesis are motivated by potential applications such as intercalation materials for Li batteries, [6] gas-storage media, cold-electron field emitters, [7] etc. Consisting of bent graphene layers (GLs), these nanomaterials possess unique electric properties due to thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
65
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(69 citation statements)
references
References 29 publications
4
65
0
Order By: Relevance
“…Conventional techniques of arc discharge, laser evaporation and CVD for the synthesis of graphitic carbon materials require very high temperature ([2000°C) and the final products normally have very low carbon yields and low surface areas because of the absence of the regular mesostructures [26][27][28]. The OMCs developed by the organic-organic self-assembly (soft-template) methods are extremely difficult to graphitize because of the nature of the phenolic-resin-based carbon precursors and high curvature energy of the continuous frameworks for the layered graphitized structure.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional techniques of arc discharge, laser evaporation and CVD for the synthesis of graphitic carbon materials require very high temperature ([2000°C) and the final products normally have very low carbon yields and low surface areas because of the absence of the regular mesostructures [26][27][28]. The OMCs developed by the organic-organic self-assembly (soft-template) methods are extremely difficult to graphitize because of the nature of the phenolic-resin-based carbon precursors and high curvature energy of the continuous frameworks for the layered graphitized structure.…”
Section: Introductionmentioning
confidence: 99%
“…We reported a high resolution TEM image of shellshaped particles shown in Fig. 4(f) [1]. From the image (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, there is a strong need to find an industrially attractive pathway to synthesize nanocarbons having varying curvatures and, moreover, to investigate their properties in many aspects such as electrical and mechanical ones. Previously, we developed a method synthesizing shell shaped carbon nanoparticles (SCNPs) having curved graphene layers in a spherical form at large scale [1,9]. In the method, an assistant oxy-hydrogen diffusion flame was utilized for preheating acetylene which undergoes CW CO 2 laser irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the latter aspect has not been well studied until now. In recent years, the studies have found that externally Energies 2017, 10, 961 2 of 11 introduced irradiation based on the different physical and chemical characteristics has good emission characteristics and high economic performance [14,15]. It has been proved that a continuous externally introduced irradiation source can increase the soot loading of the flame, influence soot morphology and the in-flame soot growth processes [16].…”
Section: Introductionmentioning
confidence: 99%